The health and social situation of the mother during pregnancy and global quality of life of the child as an adult. Results from the prospective Copenhagen Perinatal Cohort 1959-1961 - Søren Ventegodt; Trine Flensborg-Madsen; Niels Jørgen Andersen; Joav Merrick (The Scientific World Journal)
A prospective cohort study (Copenhagen Perinatal Birth Cohort 1959-61) of 7,222 persons was used in order to explore the association between the social and health situation during pregnancy and the global quality of life (QOL) of the adult child 31-33 years later. Two sets of questionnaires were used with one filled out by physicians during pregnancy and one filled out by the adult children 31-33 years later. The questionnaires included mother's situation during pregnancy and global QOL of the child at follow-up: Well-being, life satisfaction, happiness, fulfilment of needs, experience of lifes temporal and spatial domains, expression of lifes potentials and objective measures. The only indicators to have clear connections with a reduced quality of life were the cases of mother's with syphilis (8.5%), mother's congenital malformations (8.8%), low social group (6.9%) and failing contraception (3.8%). The results obtained repudiate the common notion and hypothesis that the mother's situation during pregnancy is highly important for the quality of life that the child experience as an adult. This suggest that the aspects important for quality of life later on are not found solely in early conditions, but instead more dependent on later attitude towards life of that specific person.